2006
DOI: 10.1016/j.vaccine.2006.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping synthetic peptides as vaccines

Abstract: Several vaccine strategies aim to generate cell-mediated immunity (CMI) against microorganisms or tumors. While epitope-based vaccines offer advantages, knowledge of specific epitopes and frequency of major histocompatibility complex (MHC) alleles is required. Here we show that using promiscuous overlapping synthetic peptides (OSP) as immunogens generated peptide-specific CMI in all vaccinated outbred mice and in different strains of inbred mice; CMI responses also recognized viral proteins. OSP immunogens als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…These findings confirmed that an intact TM is an important factor for in vivo viral replication. Thus, we hypothesize that the TM truncation in EIAV FDDV13 is possibly an important reason for its low level of replication [13].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings confirmed that an intact TM is an important factor for in vivo viral replication. Thus, we hypothesize that the TM truncation in EIAV FDDV13 is possibly an important reason for its low level of replication [13].…”
Section: Discussionmentioning
confidence: 97%
“…This investigation and some others found that this attenuation of virulence and the enhancement of immunogenicity were closely linked to multiple mutations in multiple viral genes. Using reverse mutations of selected sites of the vaccine strain to the corresponding sequence of the virulent strain, results from our laboratory and others determined that some mutations, especially consensus mutations that consistently existed in most of the successors once raised, in LTR [9,10], gp90 [11,12], gp45 [13], and S2 (manuscript in preparation) were responsible for the virulence of EIAV.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier mouse studies, OSP were able to induce immune responses in different strains of inbred mice as well as in the outbred mice [25, 26]; the strategy was found to be only modestly successful in RMs. This is not a stand-alone case where a mouse-tested vaccine concept could not be translated with equal success into primates/humans.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides may bind directly to MHC class II molecules of antigen presenting cells (APC) and need only partial processing for binding to MHC class I molecules. In our earlier studies, this approach generated peptide-specific cellular immune responses in all vaccinated outbred mice and also in different strains of inbred mice [25, 26]. The number of peptides made available to MHC molecules after antigen processing is limited [27, 28], but MHC molecules are potentially very promiscuous and can bind to more than million different peptides with significant affinity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have shown that overlapping synthetic peptides are capable of generating immune responses (12,13). Our recombinant overlapping peptide protein (ROP) covers the complete sequence of HIV Nef.…”
mentioning
confidence: 99%